Guide to Making Biogas from Livestock Manure using Digester made from Polyethylene Plastic (An Environmentally Friendly Technology) - Hery Koesmantoro; Karno Karno (Alliance oh Health Activists (AloHA), 2018)
In rural areas, many farmers produce livestock waste, which can pollute the environment, both air, water and soil pollution. This pollution can be eliminated by being accommodated, which at the same time can be converted into environmentally friendly energy. In this case, offered an easy and inexpensive way to make biogas using polyethylene plastic as a digester. This system can be made easily by the people without using complicated technology. Rural communities in general use biogas as stove fuel for cooking. Keywords: Livestock, Biogas, Digester, Polyethylene plastic